2005
DOI: 10.1080/09291010500079692
|View full text |Cite
|
Sign up to set email alerts
|

The role of circadian rhythm on the pharmacokinetic of methotrexate in streptozotocin-induced diabetes mellitus rats

Abstract: Chronopharmacokinetic studies have been conducted both in animals and humans. Anticancer agents are of great interest due to their narrow therapeutic range and large pharmacokinetic variability. It was reported that the pharmacokinetics of MTX showed a circadian rhythm in rats and humans. Since diabetes-induced physiological changes can affect pharmacokinetics of drugs, it was reported that MTX blood concentration in diabetic rats was higher than that of the control groups. The present study was designed to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Interestingly, we observed daily oscillations in FL–MTX concentrations in the three compartments (basolateral, apical, and intracellular), demonstrating that MTX is transported across the basal and the apical membranes of HIBCPP cells in a circadian way. This result correlates favorably with several authors who demonstrated the circadian rhythm on MTX pharmacokinetics in animal and human studies [ 57 , 58 , 59 ], supporting the idea of the effect of timing of drug administration with the pharmacokinetic parameters of MTX [ 60 ]. It is interesting to note that the peak observed in MTX transport in the basal compartment occurred around 20 h after synchronization, and the peak hAbcc4 mRNA expression in HIBCPP cells occurred around 10 h after synchronization.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, we observed daily oscillations in FL–MTX concentrations in the three compartments (basolateral, apical, and intracellular), demonstrating that MTX is transported across the basal and the apical membranes of HIBCPP cells in a circadian way. This result correlates favorably with several authors who demonstrated the circadian rhythm on MTX pharmacokinetics in animal and human studies [ 57 , 58 , 59 ], supporting the idea of the effect of timing of drug administration with the pharmacokinetic parameters of MTX [ 60 ]. It is interesting to note that the peak observed in MTX transport in the basal compartment occurred around 20 h after synchronization, and the peak hAbcc4 mRNA expression in HIBCPP cells occurred around 10 h after synchronization.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it may be concluded that free MTX or the developed vector internalization, are both circadian clock dependent. These results are in agreement with previous research where the circadian rhythmicity in MTX pharmacokinetics were demonstrated in animals and humans [33]. Notably, the internalization mediated by PEI/pDNA/MTX vector does not affect the peak of the circadian oscillation, when compared to the administration of the drug alone, considering the involvement of delivery vectors a potential strategy as cancer chronotherapy.…”
Section: The Role Of Circadian Rhythms On Cellular Uptake/internaliza...supporting
confidence: 92%
“…chronotherapy) (Levi et al 1982;Koren et al 1992;Hruesky & Bjarnason 1993;Peleg et al 1998;Lincoln et al 2000). It has been shown that pharmacokinetic characteristics and toxicity of MTX in animals and humans show a circadian rhythm (English et al 1987;Labat et al 1987;Balis et al 1989;Koren et al 1992;Premaud et al 2002;Gumustekin et al 2005). In our study, we measured peripheral blood cells and weight loss to evaluate MTX toxicity in SIDM rats and since MTX inhibits tehradydrofolate formation and influxes the cell with the same carrier molecule (RFC1) of folates, we also determined serum folic acid levels.…”
Section: Discussionmentioning
confidence: 91%
“…MTX is widely accepted for the treatment of rheumatic diseases such as arthritis, psoriasis, juvenile idiopathic arthritis, and others (Ramanan et al 2003). The chronopharmacokinetics and chronotoxicity of MTX have been investigated in rodents and humans in many studies (English et al 1987;Labat et al 1987;Balis et al 1989;Koren et al 1992;Park et al 1996;Premaud et al 2002;Gumustekin et al 2005) and it has been shown that the severity of MTX toxicity was affected by the administration time of the drug and toxicity was found to be directly correlated to peak plasma level and area under the concentration time curve (AUC) (Labat et al 1987;Koren et al 1992;Park et al 1996). However, the potential chronopharmacokinetic variations and chronotoxicity of MTX were poorly studied in SIDM rats.…”
Section: Introductionmentioning
confidence: 99%